Ancient Iran from the air - Mousavi, Ali; Stronach, David; Gerster, Georg, 1928-; Beazley, Elisabeth; Harverson, Michael; Huff, Dietrich; Sumner, William M.; Wilkinson, T. J. (Tony J.) (Philipp Von Zabern Verlag, 2012)
"This book features many of the more exceptional landscapes and monuments of Iran as seen through the lense of one of the world's foremost aerial photographers, Georg Gerster. The photographs were taken between 1976 and 1978, are presented in six chapters, each authored by one or more scholars of international repute...[The book] takes the reader on an aerial odyssey that explores the country's infinitely varied landsapes; many of the more noted sites associated with Iran's rich prehistoric past; the storied capitals of the Achaemenid and Sasanian empires; the memorable monuments of Saljuk and Safavid Isfahan; and last but not least, on a journey that celebrates the age-old virtues of Iran's largely unsung vernacular mud-brick architecture." -- Cover.